The prevalence and impact of overuse injuries in five Norwegian sports: Application of a new surveillance method - Clarsen, B.; Bahr, R.; Heymans, M. W.; Engedahl, M.; Midtsundstad, G.; Rosenlund, L.; Thorsen, G.; Myklebust, G. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Little is known about the true extent and severity of overuse injuries in sport, largely because of methodological challenges involved in recording them. This study assessed the prevalence of overuse injuries among Norwegian athletes from five sports using a newly developed method designed specifically for this purpose. The Oslo Sports Trauma Research Center Overuse Injury Questionnaire was distributed weekly by e-mail to 45 cross-country skiers, 98 cyclists, 50 floorball players, 55 handball players, and 65 volleyball players for 13 weeks. The prevalence of overuse problems at the shoulder, lower back, knee, and anterior thigh was monitored throughout the study and summary measures of an injury severity score derived from athletes' questionnaire responses were used to gauge the relative impact of overuse problems in each area. The area where overuse injuries had the greatest impact was the knee in volleyball where, on average, 36% of players had some form of complaint (95% CI 32-39%). Other prevalent areas included the shoulder in handball (22%, 95% CI 16-27%) the knee in cycling (23%, 95% CI 17-28%), and the knee and lower back in floorball (27%, 95% CI 24-31% and 29%, 95% CI 25-33%, respectively).